Isolation and Characterization of Flavonol-rich Fractions of Jatropha curcus and Evaluation of their in vivo Wound-healing Potential - Abdulazeez, Abdulrahman Monday; Khan, Muluh Emmnuel; Ilemona, Achika Jonathan; Rotimi, Larayetan; Abah, Sunday; Yahaya, Muhammad Kabir; Ugbenyo, Nicholas Omatule; Ibrahim, Abdulkarim (Journal of Science Research and Reviews, 2025)
Jatropha curcus (J. curcus) (Euphorbiaceae) is a drought resistant shrub whose leaves, latex, bark, and seed cake employed in traditional medicine to treat cuts, burns, and chronic ulcer. This study reports the isolation and structural characterization of bioactive compound(s) from the methanolic leaf extract of Jatropha curcas. Methanolic extraction of air-dried leaves was followed by silica gel column chromatography with gradient elution (hexane-ethyl acetate-methanol). Fractions were monitored by thin-layer chromatography (TLC), pooled according to similar Rf values, and crystallized to yield isolates. Purified compounds were characterized using FTIR, UV-Vis, 1H/13C NMR and LC-MS. One major yellow crystalline compound (designated TBF-19) was obtained (210.0 mg), and HRMS gave an [M]+ at m/z 198.0917 consistent with C13H11NO; the data supported the proposed structure (2-aminobenzophone as recorded in the primary notes). Wound-healing studies employed excision models in albino rats with three treatment groups (petroleum jelly, povidone iodine, and TBF-19 obtained from Jatropha Curcas). Tissue analyses included hydroxyproline and total protein assays to assess collagen deposition and tissue regeneration. The isolation workflow and spectroscopic evidence indicate that flavonoid- and phenolic-type constituents are major components responsible for the antioxidant and wound-healing properties observed in crude extracts. These findings validate the ethnomedicinal use of J. curcas and provide a basis for further bioassay-guided fractionation and detailed structure elucidation using 2D-NMR and high-resolution MS techniques.